PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN NON FINANCIAL YANG TERDAFTAR DALAM INDEKS KOMPAS 100 PERIODE 2015-2024 - Elisabeth Caroline Pawan; Yanuar Dananjaya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
The increasingly complex business environment demands companies to adopt appropriate strategies, which can be reflected through their corporate characteristics. This study aims to analyze the influence of corporate characteristics on financial performance among non financial companies listed in the Kompas 100 Index during the 2015–2024 period. A quantitative research method with regression analysis is employed, wherein the corporate characteristic variables consist of financial reporting quality, firm age, capital structure, firm size, liquidity, ratio of tangible fixed assets, and revenue growth. The research sample comprises 177 companies included in the Kompas 100 Index over a ten-year period, resulting in a total of 858 observations. The findings reveal that revenue growth has a significant effect on the companies’ financial performance, while results for the other variables vary. The study concludes that corporate characteristics play a role in explaining variations in financial performance and may serve as important considerations in corporate business strategy development. Keywords: Firm Characteristics, Growth, Capital Structure, Financial Reporting Quality, Financial Performance